Prediction of the probabilistic water leak location in underground pipelines using Monte Carlo simulation - Proença, Matheus [UNESP]; Paschoalini, Amarildo T. [UNESP]; Obata, Daniel H. S. [UNESP] (IWA Publishing, 2023)
The water loss rates in Brazil are still very concerning and cause huge financial, social, and environmental damages. Although great advances have been made in acoustic leak detection methods, some of them are intrusive or at least demand convenient access points to the pipe’s surface. Furthermore, some methods are expensive and require a highly experienced and qualified operator. Thus, the goal of this paper is to establish a benchmark using a simplistic analytical model for the ground surface analysis for leaks location, simplifying the search process carried out in water networks, and requiring minimal system inter-ference. For leak location prediction, the proposed method considered two seismic wave paths – the compressional body waves and the Rayleigh superficial waves. The traveltime curves of the compressional waves are calculated as a function of the surface wave’s experimental information. Monte Carlo Simulations were carried out to test each model’s precision consid-ering uncertainties related to the input parameters of the problem. At last, through a parametric study, the two seismic events were combined to obtain better accuracy in predicting the leakage epicenter location. In the results, the maximum absolute error found was 15 cm, and the minimum improvement obtained with the parametric study was 27.4%.
Keywords: leak location; Monte Carlo simulation; vibrations; waves propagation